On Normalistic Vague Soft Groups and Normalistic Vague Soft Group Homomorphism. (10th June 2015) - Selvachandran, Ganeshsree; Salleh, Abdul Razak
Abstract : We further develop the theory of vague soft groups by establishing the concept of normalistic vague soft groups and normalistic vague soft group homomorphism as a continuation to the notion of vague soft groups and vague soft homomorphism. The properties and structural characteristics of these concepts as well as the structures that are preserved under the normalistic vague soft group homomorphism are studied and discussed.